Gastric secretion does not affect the reliability of the 13C‐acetate breath test: A validation of the 13C‐acetate breath test by magnetic resonance imaging. Issue 2 (16th October 2012) - Kuyumcu, S.; Goetze, O.; Menne, D.; Treier, R.; Boesiger, P.; Fox, M.; Fried, M.; Schwizer, W.; Steingoetter, A.
Abstract Background 13C‐Acetate labeled meals are widely used to determine meal emptying by means of analyzing resulting 13CO2 exhalation dynamics. In contrast to the underlying metabolic processes, only few 13C breath test meal emptying studies have focused on intragastric processes that may alter 13CO2 exhalation. This work assessed the effect of enhanced gastric secretion on the reliability of half emptying time (t50) measurements by 13C‐acetate breath test. Methods 13CO2 exhalation data were acquired in a double‐blind, randomized, cross‐over gastric emptying study in 12 healthy volunteers receiving either pentagastrin or placebo intravenously. The standard method proposed by Ghoos et al. was applied to calculate t50 (t50_Ghoos) from 13CO2 exhalation data, which were compared and tested for agreement to meal half emptying times (t50_MV) from concurrent recorded MRI (magnetic resonance imaging) volume data. In addition, the accumulated gastric secretion volumes during infusion as detected by MRI (AUC_SV60) were correlated with the corresponding cumulative percent 13C doses recovered (cPDR60). Key Results t50_Ghoos and t50_MV showed a linear correlation with a slope of 1.1 ± 0.3 (r2 = 0.67), however, a positive offset of 136 min for t50_Ghoos. No correlation was detected between AUC_SV60 and cPDR60 (r2 = 0.11). Both, breath test and MRI, revealed a prolonged t50 under pentagastrin infusion with median differences in t50_Ghoos of 45[28–84] min (P = 0.002) and t50_MV of 39[28–52] min (P = 0.002). Conclusions & Inferences This study suggests that 13CO2 exhalation after ingestion of a 13C‐labeled liquid test meal is not affected by stimulated gastric secretion, but is rather reflecting the dynamics of meal or caloric emptying from the stomach.